An annotated catalogue of the Iranian Anthocoridae (Hemiptera: Heteroptera: Cimicomorpha) - Ghahari, Hassan (2009)
A total of 47 anthocorid species (Heteroptera: Anthocoridae) from 10 genera, including Amphiareus Distant, 1904, Anthocoris Fallén, 1814, Buchananiella Reuter, 1884, Cardiastethus Fieber, 1860, Dufouriellus Kirkaldy, 1906, Elatophilus Reuter, 1884, Lyctocoris Hahn, 1836, Orius Wolff, 1811, Temnostethus Fieber, 1860, and Xylocoris Dufour, 1831, are catalogued from Iran. The following fi ve species are new for Iran: Elatophilus (Euhadrocerus) hebraicus Péricart, 1967, Buchananiella continua (White, 1880), Cardiastethus fasciiventris (Garbiglietti, 1869), Orius (Heterorius) strigicollis (Poppius, 1915), and Orius (Dimorphella)tantillus (Motschulsky, 1863). Buchananiella pseudococci (Wagner, 1951), comb.nov., is transferred from the genus Cardiastethus.